Soldagem multipasse e envelhecimento térmico à 475°C de tubos de aço inoxidável superduplex UNS S32750 - Oliveira, Caroliny Gomes de (2019)
Superduplex stainless steels (SDSS) are steels widely used in the oil and gas industry due to their high mechanical strength and high corrosion resistance. These properties are due to the microstructural balance of approximately 50% for the ferrite and austenite phases present in the steel. When such material is subjected to welding and high temperature conditions which favor secondary phase precipitations, such properties are reduced as consequence of metallurgical changes. In this thesis, the multipass girth welding of UNS S32750 super duplex stainless steels thick wall pipes were joined by the GMAW process at different welding heat input levels: 0.5, 1.0 and 2.0 kJ/mm was evaluated. In addition, the 475°C aging phenomenon was studied, aiming to evaluate how the alpha prime (’) phase precipitation kinetics at this temperature would occur for different weld regions, considering fusion zone and base metal. Besides that, how this 475°C aging would affect the properties such as hardness and, especially, corrosion resistance of the welded joint. It was also studied how welding energy levels evaluated could affect the behavior of the aging phenomenon. After welding the pipes, the welded joints were characterized in as-welded condition and afterwards samples were heat treated at the temperature of 475 ° C for different exposure times: 100, 200 and 500 hours. Both conditions were analyzed by different microscopy techniques. Hardness and microhardness tests were performed to evaluate the evolution of the mechanical behavior. The corrosion resistance of the samples was also evaluated by electrochemical and immersion tests. It was observed that in this temperature range ’ phases were precipitated and for the longer time (500 h) the formation of R phase also occurred. It was possible to identify a great difference in the precipitation kinetics of these secondary phases for the regions of the weld (HAZ and FZ) when compared with the base metal (BM). The welding heat input has influenced the precipitation kinetics and the performance of the welded joint, being experimentally proved that the lower the welding heat input used the higher will be the intensity of α ' phase and phase R precipitation. This behavior is related to some factors, among them, the differences in chemical composition, especially concerning the Ni content, the higher amount of ferrite in the weld metal, the nano chemistry inhomogeneity associated with microsegregation, and residual stresses that will also affect the chemical reactivity.